The Influence of Lifestyle and Travel Motivation on Intention in Using the Nusuk Platform in the Umrah Mandiri Community - Hanifah, Nisrina Salmaa; Rozza, Sylvia; Roza, Prima (Jurnal Sosioteknologi, 2024)
Hajj and Umrah are popular in Indonesia, where most people are Muslim. Data shows that every year, the number of Hajj and Umrah pilgrims tends to increase. This is the background for the proliferation of Hajj and Umrah travel businesses in Indonesia. As technology progressed, Indonesians started to insist on conducting Umrah mandiri, or independent Umrah, independently, without the assistance of a travel agency. We conducted this study using the Nusuk platform in the Independent Umrah Community to analyze the impact of lifestyle on travel intention and motivation. We used SEM (Structural Equation Modeling) as the analysis method, with the assistance of LISREL software. The study sample consisted of 300 respondents. The findings showed that lifestyle and travel motivation variables have a positive and significant influence on the intention to use the Nusuk platform. This research not only employs a statistical tool but also analyzes the independent Umrah community's intention to utilize the new platform, a topic not previously explored in prior studies. We anticipate that this research will assist Nusuk platform managers in creating more appealing programs, thereby boosting user intentions.